Amygdala Underlies the Environment Dependency of Defense Responses Induced via Superior Colliculus - Isa, Kaoru; Tokuoka, Kota; Ikeda, Sakura; Karimi, Sara; Kobayashi, Kenta; Sooksawate, Thongchai; Isa, Tadashi (Frontiers in Neural Circuits, 2022)
In our previous study, we showed that the defense responses induced by the selective optogenetic activation of the uncrossed output pathway from the deeper layer of the superior colliculus were environment-dependent in the mouse. In a small closed box, the stimulus frequently induced flight (fast forward run-away) responses, while in a large open field, the stimulus tended to induce backward retreat responses. We tested a hypothesis that the amygdala is involved in such environment-dependency of the innate defense responses. For this purpose, we made a bilateral lesion of the amygdala with ibotenic acid injections in male mice. As a result, in the mice with lesions of substantial portions of the basolateral and basomedial complex, the flight responses in the closed box disappeared and retreat responses were mainly induced. The retreat responses on the open platform were unchanged. Classically, the amygdala has been considered to be involved in the memory-dependent contextual modulation of the fear responses. In contrast, the present results suggest a novel view on the role of the amygdala in which the amygdala plays a key role in sensing the current environmental setting for making a quick decision of action upon emergency, which is critical for survival in the natural environment.